AIRCRAFT TRAFFIC NOISE ANALYSIS AT KUALANAMU INTERNATIONAL AIRPORT MEDAN - Indrayani, Indrayani; Rajagukguk, Juniastel; Rahayu, Tri; Siregar, Rizky; Dirza, Risvan (Program Studi Fisika Universitas Negeri Jakarta, 2023)
This study was conducted to analyze and evaluate the noise generated by aircraft traffic at Kualanamu airport. Data collection was carried out by conducting a survey directly in the field by asking airport officials about the flight frequency at Kualanamu airport and measuring ground handling noise with a sound level meter. Furthermore, the data obtained were analyzed using Excel software. From the results of data processing, it is known what variables most affect ground handling noise at Kualanamu airport. Noise measurements were taken by PT. Angkasa Pura II (Persero) in an open area at Kualanamu airport, the noise that occurs is below the specified quality standard value, which is <80 dB based on the Minister of Transportation Decree No. 17 of 2005 (Sultan Syarif Kasim International Airport, while for Kualanamu International Airport there has not been a Ministry of Transportation Decree. Because both airports are international class and are located in the coastal area of Sumatra Island, it can be assumed that they have the same noise quality standards). Furthermore, noise measurements were taken by PT. Angkasa Pura II (Persero) in the domestic and international waiting room area that the noise that occurs is above the specified quality standard value, namely (45-55) dB Zone B, according to the regulation of the minister of health 718 of 1987.